2021
DOI: 10.21037/tcr-21-561
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer study of PD-1 and CTLA-4 as therapeutic targets

Abstract: Background: Immunotherapy is a new and powerful weapon against tumors, represented by inhibitors of programmed death-1 (PD-1) and cytotoxic T lymphocyte-associated protein-4 (CTLA-4). This study aimed to determine the similarities and differences between PD-1 and CTLA-4 in 33 cancers in The Cancer Genome Atlas (TCGA) and the impact of subtypes of the immune environment on tumor production and treatment.Methods: From the Xena browser, we downloaded TNM stage, immune subtypes, and tumor microenvironment scores f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The observed association between PD-1 and CTLA-4 expression might be partially attributed to the PD-1 receptor's classification within the CD28/CTLA-4 family [6]. This study's findings mirror those of the previous research, which observed parallel expression levels of CTLA-4 and PD-1 in tumor tissues, markedly exceeding those in normal tissues in patients with urothelial carcinoma [59].…”
Section: Discussionsupporting
confidence: 84%
“…The observed association between PD-1 and CTLA-4 expression might be partially attributed to the PD-1 receptor's classification within the CD28/CTLA-4 family [6]. This study's findings mirror those of the previous research, which observed parallel expression levels of CTLA-4 and PD-1 in tumor tissues, markedly exceeding those in normal tissues in patients with urothelial carcinoma [59].…”
Section: Discussionsupporting
confidence: 84%
“…Thus, our data provided a novel sight that these mutations might affect tumor progression and patients' prognosis through pyroptosis-related mechanisms. Immune checkpoint molecules such as CTLA-4, PD-1, and PD-L1 have been validated as targets in cancer immunotherapy, but few studies have explored their roles in cancer prognosis [ 38 40 ]. We discovered that the expression of immune checkpoint molecules correlated with π signature differentially between the cancer subtypes (Figures 5(c) and 5(d) ).…”
Section: Discussionmentioning
confidence: 99%
“…CCA tumors with a high PD-L1 expression tend to display more aggressive features and shorter survival times ( 124 , 125 ). CTLA-4 has also been observed to be upregulated in CCA, and of note, a significant positive correlation exists between the expression levels of PD-1 and CTLA-4 ( 126 ). An increased expression of CTLA-4 in TILs has been shown to be associated with malignant characteristics and poor survival outcomes in iCCA.…”
Section: Immune Escape Of Cholangiocarcinomamentioning
confidence: 99%